Neutron total cross-section of hydrogenous and deuterated 1- and 2-propanol and n-butanol measured using the VESUVIO spectrometer - Rodriguez Palomino, Luis Alberto; Dawidowski, Javier; Marquez Damian, Jose Ignacio; Cuello, Gabriel Julio; Romanelli, G.; Krzystyniak, M. (Elsevier Science, 2017)
Fil: Rodriguez Palomino, Luis Alberto. Comisión Nacional de Energía Atómica; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina